Scale up of Anaerobic Fluidized Bed Reactors - Öztürk, İ.; Idris, A. H. (Springer Netherlands, 1992)
In this study a 12.5 1 laboratory-scale Anaerobic Fludized-Bed Reactor (AFBR) was set up according to the principle of geometric similarity based on a pilot-reactor with a volume of 70 1(1). Performance evaluation, tracer analysis and kinetic studies were carried out on both AFBR’s. The data were used for the comparison between the two differently sized AFBR’s. It was shown that the criteria for scale-up namely, geometric, biological and dynamic similitude were the most dominant in AFBR. However, the main difficulty with the prediction of process behaviour in the larger scale fluidized bed was due to biological variation (2), (1).